Implementation of Bureaucratic Reform and Development of Integrity Zones: Study at State Civil Service Agency - Agustina Dorsima Dolonseda; Stefanus Sampe; Very Y. Londa (Journal La Bisecoman, 2024)
Implementing the construction of an integrity zone is one of the steps taken by the government related to bureaucratic reform. The State Civil Service Agency is a government institution responsible for the development and implementation of State Civil Service Management. This research was conducted to describe the implementation of bureaucratic reform that needs to be carried out by the Regional Office XI BKN to move towards a Clean and Serving Bureaucratic Region. By using a qualitative design, it was found that the bureaucratic reform that had been carried out by the Regional Office.